2018
DOI: 10.1016/j.jasrep.2017.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Visibility analysis of the Roman communication network in southern Scotland

Abstract: This paper uses GIS and visibility analysis to examine if Rubers Law fits into the known Roman communication and infrastructure network of towers, forts, camps and roadways in southern Scotland. Rubers Law is a prominent hill in the Scottish Borders with an extensive archaeological history, and the discovery of approximately 30 Roman building stones on the summit in the early 20th century led to the conclusion that it had been the site of a Roman signal station, despite a lack of concrete evidence for a Roman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Beginning with the topography, Digital Terrain Models (DTM) -apart from the most direct representations of height, slope and orientation-can be employed for analysing the visibility -either between specific points or to show complete viewsheds from a network of watchtowers (e.g. Llobera, 2007;Rua, Gonçalves, & Figueiredo, 2013;Deidda, Musa, & Vacca, 2015;Earley-Spadoni, 2015, Ferreira-Lopes & Molina, 2018Murphy, Gittings, & Crow, 2018)-, as well as for the obtention of the minimum cost paths and, hence, to retrace lost routes (Canosa-Betés, 2016) or to represent different groups of transit points which can explain episodes that may have happened during the journeys (Ferreira-Lopes & Pinto, 2018). Another possibility is to define an index of "defensiveness" based on the relief of the surrounding terrain that can explain the location of defensive structures and settlements.…”
Section: Geographic Information Systemsmentioning
confidence: 99%
“…Beginning with the topography, Digital Terrain Models (DTM) -apart from the most direct representations of height, slope and orientation-can be employed for analysing the visibility -either between specific points or to show complete viewsheds from a network of watchtowers (e.g. Llobera, 2007;Rua, Gonçalves, & Figueiredo, 2013;Deidda, Musa, & Vacca, 2015;Earley-Spadoni, 2015, Ferreira-Lopes & Molina, 2018Murphy, Gittings, & Crow, 2018)-, as well as for the obtention of the minimum cost paths and, hence, to retrace lost routes (Canosa-Betés, 2016) or to represent different groups of transit points which can explain episodes that may have happened during the journeys (Ferreira-Lopes & Pinto, 2018). Another possibility is to define an index of "defensiveness" based on the relief of the surrounding terrain that can explain the location of defensive structures and settlements.…”
Section: Geographic Information Systemsmentioning
confidence: 99%
“…A number of recent studies have applied visibility analysis to the investigation of ancient defensive systems and specifically to watchtower networks (Earley-Spadoni, 2015;Topouzi et al, 2002, to name just a few). Fundamentally, visibility analysis measures what can be seen from an observation point-usually a site-and this information is used to address questions relating to site placement, communication, and defensibility (Bongers, Arkush, & Harrower, 2012;Marsh & Schreiber, 2015;Murphy, Gittings, & Crow, 2018). Typically, visibility analysis entails calculating the viewsheds of one or more sites, and determining lines of sight between pairs of sites.…”
Section: Visibility Analysis and Directional Visibility Conesmentioning
confidence: 99%
“…Visibility studies frequently assume ideal conditions regarding weather, time of day, and visual acuity of the observer, and this can lead to an overestimation of the distance limits for search radii (Rua, Gonçalves, & Figueiredo, 2013). Recognizing that visibility will inevitably decay over distance due to a wide range of factors, fuzzy viewshed analysis has developed as a means to statistically account for this decline in detection rates (Fisher, 1994;Rášová, 2014;Ogburn, 2006;Murphy, Gittings, & Crow, 2018). Despite the advances presented by fuzzy viewsheds, there remains considerable variability in the selected values for search radii in visibility studies, which can range from 4 km (Turchetto & Salemi, 2017) to 60 km (Murphy, Gittings, & Crow, 2018).…”
Section: Determining Visibility Radiusmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study by Lee (2010) has potentially identified the archaeological remains of the network of signaling stations that would have comprised this early warning system. Fire-based signaling beacons were also used along the fortified borders of the major Eurasian empires, such as the Roman frontier in northern Britain (Murphy et al 2018).…”
Section: Signaling Infrastructurementioning
confidence: 99%